An Analysis of Impoliteness Used by Male and Female Character in Wolf of the Wall Street Movie - Sudewa, Sudewa; Ardi, Havid (English Language and Literature, 2021)
Impoliteness is a bad attitude and occurred when the speaker face attacks the hearer and the hearer receives the face attack from the speaker or both of them. Categories of impoliteness based on (Culpeper, 2016) are bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mocking politeness and withhold politeness. This research is aimed to find out type impoliteness used by the male and female characters in Wolf of the Wall Street movie. This research is descriptive comparative. The data were collected from all texts which are transcribed from spoken ones used by the male and female characters in the movie Wolf of the Wall Street. The result showed that the total of impoliteness is 46, with 31 impoliteness from male characters and 15 impoliteness from female characters. Then, in the category of purpose of power, there were only 13 purpose of power in male characters, but none in female characters.